(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2023)
In recent decades, heart disease has become a major concern, and many people have died because of various health issues, heart disease is a critical issue in the health sector. We propose a monitoring system that include AD8232 ECG sensor based on the Arduino to monitoring the people that have heart disease. The AD8232 ECG sensor is a small chip that measures heart electrical activity, also can be recorded the signals and analyzed. In this paper, Electrocardiogram(ECG) with AD8232 ECG sensor are used to show ECG graph through the monitoring of the patients, it used to help diagnose various heart conditions. The proposal scheme is simplified the process of connecting and show the signals on LCD screen. The results are shown the electrical activity, which used to diagnose the heart conditions for the different ages. The simulation of the proposal scheme by using proteus virtual system modeling; the results show the ECG graph. In addition, in the practice side, it is connected and applied on the human body to show the results for the monitoring that is represented the ECG signals